Integrin α8 Is Abundant in Human, Rat, and Mouse Trophoblasts - Herdl, Sebastian; Hübner, Hanna; Volkert, Gudrun; Marek, Ines; Menendez-Castro, Carlos; Nögel, Stephanie; Rübner, Matthias; Rascher, Wolfgang; Hartner, Andrea; Fahlbusch, Fabian B. (Reproductive Sciences, 2017)
OBJECTIVE: Integrins exert regulatory functions in placentogenesis. Null mutation of certain integrin α subunits leads to placental defects with subsequent fetal growth restriction or embryonic lethality in mice. So far, the placental role of α8 integrin remains to be determined. METHODS: Localization of α8 integrin and its ligands, fibronectin (FN) and osteopontin (OPN), was studied by immunohistochemistry in human, rat, and mouse placenta. The vascularization of the placental labyrinth layer of α8 integrin-deficient mice was determined by CD31 staining. In humans, α8 integrin expression was assessed via real-time polymerase chain reaction in healthy placentas, in the placental pathologies such as intrauterine growth restriction (IUGR), preeclampsia, and HELLP-syndrome (hemolysis, elevated liver enzymes, low platelet count), as well as in primary extravillous trophoblasts (EVT) and villous trophoblasts. RESULTS: In humans, α8 integrin was detected in first and third trimester syncytiotrophoblast and EVT. Although OPN showed the same localization, FN was observed in EVT only. No expressional changes in α8 integrin were detected in the placental pathologies studied. Rodent placenta showed α8 integrin expression in giant cells and in the labyrinth layer. The localization of OPN and FN, however, showed species-specific differences. Knockout of α8 integrin in mice did not cause IUGR, despite some reduction in labyrinth layer vascularization. CONCLUSION: α8 Integrin is expressed in functional placental compartments among its ligands, OPN and/or FN, across species. Although this may point to a regulatory role in trophoblast function, our data from α8 integrin-deficient mice indicated only mild placental pathology. Thus, the lack of placental α8 integrin seems to be largely compensated for.
EVALuna2:34006